2015
DOI: 10.1002/ejic.201500389
|View full text |Cite
|
Sign up to set email alerts
|

Electro‐Assisted Reduction of CO2 to CO and Formaldehyde by (TOA)6[α‐SiW11O39Co(_)] Polyoxometalate

Abstract: We report here on the multiproton-multielectron electrochemical reduction of CO 2 in homogeneous solution by using (TOA) 6 [α-SiW 11 O 39 Co(_)] (TOA = tetraoctyl ammonium; _ = vacant position in the coordination sphere of Co) as an electrocatalyst. First, the electrochemical behavior of (TOA) 6 -[α-SiW 11 O 39 Co(_)] was analyzed in detail by cyclic voltammetry in dichloromethane, studying the influence of the pres- [a]3642 ence of protons and/or CO 2 . These preliminary results were further used to optimize … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 42 publications
1
26
0
Order By: Relevance
“…Emission of carbon dioxide (CO 2 ) from consumption of fossil fuels has led to serious global climate issues, ocean acidification and other environmental concerns. International attention to those concerns have stimulated governmental regulations and extensive research efforts . Among various solutions, photochemical reduction of CO 2 into high‐value chemicals and fuels using solar energy is ultimately a sustainable solution to the problems .…”
Section: Introductionmentioning
confidence: 99%
“…Emission of carbon dioxide (CO 2 ) from consumption of fossil fuels has led to serious global climate issues, ocean acidification and other environmental concerns. International attention to those concerns have stimulated governmental regulations and extensive research efforts . Among various solutions, photochemical reduction of CO 2 into high‐value chemicals and fuels using solar energy is ultimately a sustainable solution to the problems .…”
Section: Introductionmentioning
confidence: 99%
“…Surprisingly, only a few reports of CO 2 reduction with POMs exists: while in 1990 Yamase proposed the photoreduction in water of CO 2 to CH 4 catalyzed by [PTi 2 W 10 O 40 ] 7– , Neumann published more recently that [RuSiW 11 O 39 ] 5– promotes the photoreduction of CO 2 to CO in toluene . Following Kozik's work,, we have reported that [CoSiW 11 O 39 ] 6– is an electrocatalyst in dichloromethane for the two electron reduction of carbon dioxide to CO, but also, in the presence of acid, to a very seldom observed four electron reduction product, formaldehyde . Besides being the catalytic species, another role for the POM as an electron/proton relay has also been recently proposed …”
Section: Introductionmentioning
confidence: 80%
“…Besides the necessity to work in a non‐coordinating apolar solvent such as dichloromethane, another drawback of [CoSiW 11 O 39 ] 6– as an electrocatalyst for CO 2 reduction is its low activity . To move forward, we aimed at investigating the association of the POM properties with those of a known catalyst, preferably in more “classical” solvents like acetonitrile or even water.…”
Section: Introductionmentioning
confidence: 99%
“…Other electrochemical approaches gave Faradaic efficiencies between 0.08% and 25% for formaldehyde derived from CO2 using polyoxometalate as catalyst material. 64 Scheme 8. Electrocatalytic reduction with Boron doped-diamond electrode with highest efficiency for formaldehyde at -1.7V.…”
Section: Direct Formaldehyde Synthesismentioning
confidence: 99%